Farmed fish welfare in Egypt: Surveying current practices and future directions for tilapia culture - Charlotte Flores; Christopher Bryant; Mohamed Bakr; Wasseem Emam (Aquaculture Reports)
This study aimed to map the current status of farmers' knowledge, attitudes, and practices (KAPs) vis-à-vis animal welfare in the Egyptian tilapia farming sector. To this end, a survey was conducted of tilapia farmers across different regions, examining their level of training and knowledge as well as their farming practices including feeding, water changes and biosecurity measures.We found that just 11 % of the surveyed tilapia farmers had received any sort of training on the importance of animal welfare whilst 76 % said they could benefit from such training. Farmers perceived maintaining good water quality as the most important metric for achieving good tilapia welfare. However, they were significantly less willing and able to intervene on this factor compared to other factors such as changing feeding practices, minimising handling, and carrying out veterinary checks.In addition, we found evidence of better production outcomes for farmers that had received welfare training, with significantly fewer of them reporting high mortality rates and significantly lower reported frequency of poor growth. Most farmers expected the Egyptian tilapia production sector to continue to grow and intensify. This survey identified a need for establishing minimum animal welfare standards in Egyptian tilapia farming either through regulators or certification schemes. There is also a clear need for establishing training programmes that cover animal health and welfare aspects in aquaculture.